2022
DOI: 10.1021/acs.jmedchem.2c00448
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold Hopping Strategy to Identify Prostanoid EP4 Receptor Antagonists for Cancer Immunotherapy

Abstract: Cancer cells can effectively suppress the natural immune response in humans, and prostaglandin E2 (PGE2) is a key mediator in the development of tumor cell resistance to immunotherapy. As a major contributor to PGE2-elicited immunosuppressive activity, the EP4 receptor promotes tumor development and progression in the tumor microenvironment, and the development of selective and potent EP4 receptor antagonists should have promising potential for tumor immunotherapy. Aiming at improving the drug-like properties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Similar safety evidence of a selective EP4 antagonist (grapiprant/Galliprant ® for animal health) was also demonstrated in field studies using dogs with disease (31). Recently, other EP4 antagonists have been developed (32,33). AAT-008 has a great binding potency for EP4 receptors and has more than 1,000-fold higher selectivity than other prostaglandin receptors (11).…”
Section: Discussionmentioning
confidence: 60%
“…Similar safety evidence of a selective EP4 antagonist (grapiprant/Galliprant ® for animal health) was also demonstrated in field studies using dogs with disease (31). Recently, other EP4 antagonists have been developed (32,33). AAT-008 has a great binding potency for EP4 receptors and has more than 1,000-fold higher selectivity than other prostaglandin receptors (11).…”
Section: Discussionmentioning
confidence: 60%
“…In Schild plot analysis, the p A 2 value was 9.064 and the slope was 1.073 (Figure H). Calcium flux assay is a universal and reliable method for evaluating GPCR activation and all of the four EP subtypes were shown to induce calcium flux in CHO-Gα 16 cells. , Specifically, compound 14 had an IC 50 value of 2.1 ± 0.7 nM against EP4 in calcium flux assay (Figure S1A), while it had no antagonistic activity against EP1-3 receptors (IC 50 > 10 000 nM) (Figure I). In summary, these results demonstrated that compound 14 is a highly potent and selective competitive EP4 antagonist.…”
Section: Resultsmentioning
confidence: 99%
“…A CHO cell line stably expressing the Gα 16 protein, CHO-Gα 16 , was used for calcium flux assay as described in our previous study. , In brief, CHO-Gα 16 was transfected with the expression vector of individual EP receptor subtypes using PEI and seeded into 96-well plates (3.0 × 10 4 cells/well) (Corning, USA) at 37 °C. After 24 h of incubation, transfected cells were loaded with Calcium-5 assay kit reagent (Molecular Devices, USA) for 45 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…E7046 diminished myeloid immunosuppression and synergized with Treg-reducing IL-2–diphtheria toxin fusion protein in restoring antitumor immunity. A few EP4 antagonists, including LY3127760, were reported for cancer models. , A scaffold hopping strategy was adopted to identify EP4 antagonists and applied for cancer immunotherapy . EP4 antagonist L001 ( 7 ) was demonstrated to suppress pancreatic cancer in animal models .…”
mentioning
confidence: 99%